Measuring the impact of external exchange rate shocks on the performance indicators of the Iraqi economy: using the Kaldor square - Munaf Marza Neama; Mustafa Kamel Rasheed (International Forum of Researchers and Lecturers, 2025)
This research is an attempt to analyze and measure the impact of structural shocks to the US dollar exchange rate on the performance indicators of the Iraqi economy during the limited period (2004 to 2022) using the Kaldor square framework, which is based on four main components (economic growth, inflation, unemployment, and trade balance). Analytical and quantitative methods were rummage-sale to reveal the countryside of the relationship between these variables, through analyzing annual data and key economic indicators, using standard economic models and applying the (SVAR) technique. The study concluded that structural shocks to the exchange rate had varying effects on the components of the Kaldor square. The results showed a strong relationship between the exchange rate, economic growth, and the trade balance, while its impact on unemployment and inflation varied depending on the time period and political and economic developments. The study recommends adopting flexible monetary and fiscal policies that contribute to reducing exchange rate volatility and enhancing macroeconomic stability, which positively impacts sustainable structural growth.Inflation